The Effect of Fatcas Act On Banks Obligation to Keep Clients Banking Secret in Iraq - جاسم اسيل باقر (Journal of Legal Sciences, 2020)
Tax compliance is one of the most important programs that countries seek to combat a tax evasion. the congress of u.s. enactrd an act which guarantes the us: government fighting against tax evasion of those citizens who lives outside its territory. this act is called: (the foreign account tax compiliance act), FATCA 2013. the idea of this law is embodied in commitment of all non – us foreign financial institutions and bank sin in countries that have memorand am of mutel cooperation with the U.S government to diselose their records for internal revenue service and to report in formation about accounts by u.s. account holders so that (IRS) can with hold on pay ments to certiav investors according to the u.s. legal rules .